STRATEGI BALAI PEMASYARAKATAN KELAS SATU SURABAYA DALAM MEMPERSIAPKAN NASIONALISASI HUKUM PIDANA - Addelia Aizah Rachma; Eka Nanda Ravizki (Yustitia, 2025)
Laws must continue to be updated in order to keep up with the dynamics of societal development. This also applies to the current Indonesian Criminal Code so that the determination of punishment can effectively achieve community welfare. The purpose of punishment in Articles 51-52 of the National Criminal Code shows that punishment is not only aimed at providing a sense of deterrence, but also as rehabilitation for prisoners. In this case, BAPAS plays a role in guiding correctional clients so they can return to society. However, the scope of the work area is too broad so that coaching cannot be maximized. BAPAS Class One Surabaya has a working area covering five regions including Surabaya, Sidoarjo, Gresik, Jombang and Mojokerto. The method used in this research is empirical juridical conducted through interviews. The collected data will be analyzed descriptively-analytically. The research results show that to optimize the recovery of correctional clients, BAPAS formed Griya Abhipraya as a forum for correctional clients to develop their independence and skills.